Examining the effect of affective commitment to the supervisor on nurses' psychological health as a function of internal locus of control. (12th March 2017) - Huyghebaert, Tiphaine; Gillet, Nicolas; Becker, Caroline; Kerhardy, Solene; Fouquereau, Evelyne
Abstract : Aim: This research aimed to examine how affective commitment to the supervisor related to nurses' well‐ and ill‐being, and to explore the moderating function of internal locus of control in these relationships. Background: Little is known about the effects of affective commitment to the supervisor on well‐ and ill‐being, even less so in the nursing profession. Moreover, previous studies suggested that nurses' psychological reactions to their work environment might vary as a function of their individual characteristics. Methods: This cross‐sectional research used a questionnaire survey to explore the hypothesised relationships in a sample of 100 female certified nursing assistants. Results: The results revealed that affective commitment to the supervisor was most strongly related to job satisfaction and well‐being, and associated with lower levels of emotional exhaustion, when the internal locus of control was high. Conclusions: The present study emphasises the importance of a high quality relationship between nurses and their supervisors in order to promote their psychological health, and underscores the importance of individual characteristics. Implications for nursing management: This research indicates how nurses' psychological health could be promoted by fostering their affective commitment to the supervisor. It also emphasises that managers' relationships with their subordinates should be adjusted as a function of nurses' individual characteristics.